2016
DOI: 10.1371/journal.pone.0152840
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of SMT C1100, a 2-Arylbenzoxazole Utrophin Modulator, following Single- and Multiple-Dose Administration to Pediatric Patients with Duchenne Muscular Dystrophy

Abstract: PurposeSMT C1100 is a utrophin modulator being evaluated as a treatment for Duchenne muscular dystrophy (DMD). This study, the first in pediatric DMD patients, reports the safety, tolerability and PK parameters of single and multiple doses of SMT C1100, as well as analyze potential biomarkers of muscle damage.MethodsThis multicenter, Phase 1 study enrolled 12 patients, divided equally into three groups (A–C). Group A were given 50 mg/kg on Days 1 and 11, and 50 mg/kg bid on Days 2 to 10. Group B and C received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 14 publications
1
50
2
Order By: Relevance
“…The use of SMT C1100 translated into improvement of muscle morphology and functionality, with utrophin detected also in heart and diaphragm in mdx mice [43]. A phase I clinical trial showed that SMT C1100 is safe and well tolerated [44]. Neuregulin 1/heregulin beta 1 (NRG1/HRGβ1) is a factor that controls the expression of utrophin at the NMJ, through the interaction with erbB/HER receptor and the utrophin A promoter, after GABPα/β activation by the ERK pathway [45].…”
Section: Induction Of Utrophin Expressionmentioning
confidence: 99%
“…The use of SMT C1100 translated into improvement of muscle morphology and functionality, with utrophin detected also in heart and diaphragm in mdx mice [43]. A phase I clinical trial showed that SMT C1100 is safe and well tolerated [44]. Neuregulin 1/heregulin beta 1 (NRG1/HRGβ1) is a factor that controls the expression of utrophin at the NMJ, through the interaction with erbB/HER receptor and the utrophin A promoter, after GABPα/β activation by the ERK pathway [45].…”
Section: Induction Of Utrophin Expressionmentioning
confidence: 99%
“…Glucocorticoid treatment is the current standard of care which delays the loss of ambulation by 3-4 years 7,8 but shows no long treatment benefit and is often associated with debilitating side effects [9][10][11] . The urgency to seek a therapy for DMD has resulted in parallel efforts to develop exon skipping 12,13 , termination codon read through 14 , dystrophin gene replacement or editing therapies 15,16 and non-dystrophin strategies [17][18][19] such as utrophin modulation 20,21 . However, despite the recent accelerated approval of Exondys 51 (eteplirsen) in US, disappointing clinical trials results 22 and failure of approval from the FDA for Ataluren 23 and Kyndrisa 24 drugs rekindle discussions about clinical trials designs and endpoints.…”
mentioning
confidence: 99%
“…In adult muscles, dystrophin is more prevalent than utrophin. Utrophin is localized to the neuromuscular and myotendinous junctions and upregulated only when a muscle is being repaired . The expression and prevalence of utrophin is increased in DMD but not to the extent that would decrease dystrophic symptoms .…”
Section: Utrophin Modulatorsmentioning
confidence: 99%